INTERNATIONAL MEANS OF POST-CONFLICT SETTLEMENT: THE EXPERIENCE OF BOSNIA AND HERZEGOVINA - Lytvyn, О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
This paper considers the mechanisms of post-conflict state building using the  example of Bosnia and Herzegovina. The analysis of applied non-violent and coercive tools and their effectiveness at the time of application are analyzed. The role of third parties in the settlement policy and the role of institutes in peacebuilding have been examined. There was determined which of the mechanisms were effective and yielded a positive result for further development.